ANALISIS PERBANDINGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN METODE ACTIVITY BASED COSTING DALAM MENETAPKAN HARGA JUAL RUKO PADA PT. MEGASURYA NUSALESTARI - Sugawa, Sri Indriani; Ilat, Ventje; Kalalo, Meily (Universitas Sam Ratulangi, 2018)
Cost of goods means the amount of expenses and expenses that are allowed directly or indirectly to produce goods or services in conditions and places where they can be used or sold. PT. Megasurya Nusalestari uses the Full Costing Method to calculate the cost of production in making a decision to determine the selling price of a shophouse. Actvity Based Costing method is a cost information system that is oriented to providing complete information about activities. This study aims to analyze the comparison of cost of goods manufactured using the full costing method and the activity based costing method to determining the selling price of a shophouse. This type of research used in this thesis research is a comparative descriptive method that is comparing the similarities and differences between two or more facts and the nature of objects that are examined based on a certain frame of mind. The results of the study obtained that the activity based costing method produces more accurate data in each loading of resources in the shophouse production process at PT. Megasurya Nusalestari, so that the selling price generated by the full costing method is higher for the standard type, but for the corner and middle type types the resulting selling price is lower than the activity based costing method, it is because the full costing method imposes factory overhead costs on each product is only charged to one cost driver.Keywords: Full Costing Method, Activity Based Costing Method, Selling Price